CO2-C losses and carbon quality of selected Maritime Antarctic soils - De Souza Carvalho, Juliana Vanir; De Sámendonça, Eduardo; La Scala Jr., Newton [UNESP]; Reis, César; Reis, Efrain Lázaro; Schaefer, Carlos E.G.R. (Cambridge University Press (CUP), 2013)
Polar Regions are the most important soil carbon reservoirs on Earth. Monitoring soil carbon storage in a changing global climate context may indicate possible effects of climate change on terrestrial environments. In this regard, we need to understand the dynamics of soil organic matter in relation to its chemical characteristics. We evaluated the influence of chemical characteristics of humic substances on the process of soil organic matter mineralization in selected Maritime Antarctic soils. A laboratory assay was carried out with soils from five locations from King George Island. We determined the contents of total organic carbon, oxidizable carbon fractions of soil organic matter, and humic substances. Two in situ field experiments were carried out during two summers, in order to evaluate the CO2-C emissions in relation to soil temperature variations. The overall low amounts of soil organic matter in Maritime Antarctic soils have a low humification degree and reduced microbial activity. CO2-C emissions showed significant exponential relationship with temperature, suggesting a sharp increase in CO2-C emissions with a warming scenario, and Q10 values (the percentage increase in emission for a 10°C increase in soil temperature) were higher than values reported from elsewhere. The sensitivity of the CO2-C emission in relation to temperature was significantly correlated with the humification degree of soil organic matter and microbial activity for Antarctic soils. © 2012 Antarctic Science Ltd.
Keywords: C sequestration; C stocks; CO2 emission; permafrost; polar soils; carbon dioxide; carbon emission; carbon sequestration; fractionation; global climate; global warming; humic substance; humification; mineralization; polar region; soil carbon; soil organic matter; soil temperature; terrestrial environment; Antarctica; King George Island; South Shetland Islands